Mismatch between the origin of premature ventricular complexes and the noncompacted myocardium in patients with noncompaction cardiomyopathy patients: involvement of the conduction system?. Issue 2 (29th August 2016) - Van Malderen, Sophie; Wijchers, Sip; Akca, Ferdi; Caliskan, Kadir; Szili‐Torok, Tamas
Abstract : Background: Noncompaction cardiomyopathy (NCCM) is considered to be the result of an arrest in the normal myocardial embryogenesis. The histological, developmental, and electrophysiological explanation of ventricular arrhythmias in NCCM is still unknown. The aim of this study was to determine the origin of premature ventricular contractions (PVCs) in NCCM and to identify any predominant arrhythmic foci. Methods: Retrospective data from our NCCM registry including 101 patients were analyzed. A total number of 2069 electrocardiograms (ECGs) were studied to determine the origin of PVCs. Echocardiographic data were analyzed in patients with PVCs in all 12 leads. Segments affected by noncompaction (NC) were compared with the origin of PVCs. Results: PVCs were documented in 250 ECGs from 55 (54%) patients. Thirty‐five ECGs recorded PVCs on all 12 leads and the origin of 20 types of PVCs could be determined. Ninety‐five percent of PVCs did not originate from left ventricular NC myocardial areas and two PVCs (10%) had a true myocardial origin. All other PVCs originated from structures such as the outflow tracts (8/20), the fascicles (7/20), especially the posteromedial fascicle (6/20), and the mitral and tricuspid annulus (3/20). Conclusions: Our data suggest that PVCs in NCCM mainly originate from the conduction system and related myocardium.